Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Pemberian Bantuan Usaha Mikro dengan Menggunakan Metode SAW dan SMART - Dandi Putra; Agung Triayudi; Agus Iskandar (Journal of Computer System and Informatics (JoSYC), 2023)
The purpose of this business capital assistance program is to help people develop businesses that were previously affected by the Covid-19 pandemic which caused small businesses such as street vendors and home businesses to experience a decrease in income. This program aims to help small and medium enterprises (MSMEs). Potential beneficiaries are currently still selected through meetings held by village heads, which require a longer decision-making process.Therefore it is very important to create a new system that can be used to assist those who are eligible to receive targeted funds. In this study, a decision support system application was made to make it easier for village heads to determine candidates who are entitled to receive assistance according to the criteria. A decision support system is a solution that can be used to find out the results of the selection of MSME beneficiaries using the SAW and SMART methods. The SAW and SMART methods use 10 alternative data to provide an assessment of the final result by ranking from the highest to the lowest alternative value, showing that the two methods produce data that is accurate and suitable when applied as a ranking. The calculation results generated by the system that has been tested with the results of manual calculations, both show the same results.